Richness and composition of the Cladocera community (Crustacea: Branchiopoda) from the Maranhão State, Northeast Brazil - Santos, Arielly S.; Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M. A.; Andrade, Daniel S.; Mugnai, Riccardo (Zootaxa, 2021)
The state of Maranhão, northeast Brazil, has four different biomes. The water bodies in Maranhão belongs to three hydrographic regions. Thus, the state potentially contributes to a high biodiversity. Despite that, in the state, the study of cladocerans can still be considered incipient. This work aims to summarize the list of species of cladocerans in the state of Maranhão, including the results of new fauna surveys. We report ten new species records for the state, two species represent the new record of the genus Pseudosida Herrick, 1884. The results found point to the occurrence of 82 valid taxa in the state of Maranhão.